Optical properties of multi-stacked BaTiO3/SrTiO3 thin films synthesized via chemical method. Issue 13 (1st July 2021) - Ramezani, Alireza; Abdizadeh, Hossein; Golobostanfard, Mohammad Reza
Abstract: In this work, the BaTiO3 and SrTiO3 thin films as well as BaTiO3 /SrTiO3 lamellar composites are synthesized via sol-gel spin-coating method. The formation of corresponding phases from their sols is investigated by virtue of X-ray diffraction on their powders, which confirms the formation of tetragonal structure for BaTiO3, but cubic structure for SrTiO3 . The field emission scanning electron microscopy images show that crack-free films with different morphologies are formed in each sample. Likewise, by changing periodicity of the samples, the morphology of the composite samples is changed. As the number of layers increases from 1 to 20, the band gap reduces from 4.38 eV to 4.10 eV for BaTiO3 samples and from 4.13 eV to 3.80 eV for SrTiO3 samples confirmed by UV–Vis spectra. The band gap of periodicity = 1 sample is higher than that of BaTiO3, while band gaps of periodicity = 2 and 5 composites mount between those of BaTiO3 and SrTiO3 . In addition, the refractive indices of multi-stacked composites are about 0.2 lesser than refractive indices of BaTiO3 sample in high wavelengths. The periodicity dependence of optical frequency dielectric constant, dielectric loss, impedance, Urbach tail, extinction coefficient, and electric modulus of multi-stacked composites are also studied. Graphical abstract: Image 1